2018
DOI: 10.1039/c8tx00207j
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the respiratory chain by toxicants: beyond the toxicities to mitochondrial morphology

Abstract: The mitochondrion is an important subcellular target of environmental toxicants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Third, low levels of PM 2.5 exposure may stimulate the immune system, while high levels may compromise immune function, as environmental genotoxicants have been shown to exert different effects (i.e. harmful or beneficial) depending on molecular and ecological factors [45][46][47]. This study shows that the impacts of these air pollutants on HFMD are complex and require further exploration, particularly of the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 89%
“…Third, low levels of PM 2.5 exposure may stimulate the immune system, while high levels may compromise immune function, as environmental genotoxicants have been shown to exert different effects (i.e. harmful or beneficial) depending on molecular and ecological factors [45][46][47]. This study shows that the impacts of these air pollutants on HFMD are complex and require further exploration, particularly of the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 89%
“…For the first time, we herein identified mRNAs and lncRNAs that were abnormally expressed in human lung fibrosis induced by silica exposure, which exhibits complex pathological changes; no effective therapy is available. Biomarkers discovered via mRNAs and lncRNAs analysis might facilitate diagnosis and therapy [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria16S:Silva (release 128, http://www.arb-silva.de) was used for species identification and analysis. Phylogenetic tree analysis was conducted using the neighbor-joining method, and multiple comparisons were performed using PyNAST (version 1.2.2, http://biocore.github.io/pynast/) and ClustalW2 [10] (http://www.ebi.ac.uk/Tools/msa/clustalw2/).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have identified that inhalation of free silicon dioxide or silica is the cause of silicosis, and that the main clinical pathological feature is progressive pulmonary fibrosis [7]. The underlying mechanisms may involve silica-induced cytotoxicity of macrophages, activation of leukocytes to produce reactive oxygen free radicals, and damage to alveolar epithelial cells to induce fibroblast proliferation [810]. However, the exact mechanism of progressive pulmonary fibrosis in silicosis remains unclear.…”
Section: Introductionmentioning
confidence: 99%